THE INFLUENCE OF PRICE, PRODUCT QUALITY AND BRAND IMAGE ON INTEREST IN REPURCHASING KING BANANA FAN MEDAN IGOR IN MAKASSAR - Tasya Tjiadinegoro; J.E Sutanto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
The aim of this research is to determine the influence of price, product quality and brand image on interest in repurchasing fan bananas at Raja Banana Fan Medan in Igors. The population used in this research were people who had purchased Medan fan fried bananas in Makassar with a sample of 120 people, so the sampling technique used was purposive sampling technique. Data collection was carried out using an online research instrument (Google Form) using a Likert scale. The independent variables studied include price, product quality and brand image, as well as the dependent variable repurchase interest. Researchers processed the data using IBM SPSS 25 software to test the proposed hypothesis. The results of multiple linear regression analysis show that the three independent variables have a significant positive effect on repurchase intention both simultaneously and partially, so that the fourth hypothesis is accepted. The results of this research imply the importance of price adjustments, improving product quality and brand image on repurchase interest in Raja Pisang Goreng Fan in Makassar.